(adsbygoogle = window.adsbygoogle || []).push({}); 1. The problem statement, all variables and given/known data

Sn=1-3+5-7...+(-1)^n(2n+1)

2. Relevant equations

Show that Sn=(-1)^n(n+1)

3. The attempt at a solution

S(n+1)=Sn+(-1)^(n+1)*(2n+3) = (-1)^n*(n+1)+ (-1)^(n+1)*(2n+3)

S(n+1)= (-1)^(n+1)*[(2n+3)-(n+1)] (because (-1)^(n+1)= - (-1)^n )

S(n+1)=(-1)^(n+1)*(n+2)

is that correct proof

**Physics Forums | Science Articles, Homework Help, Discussion**

Join Physics Forums Today!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Problem on induction

**Physics Forums | Science Articles, Homework Help, Discussion**